How do entrepreneurial portfolios respond to income taxation? - Frank M. Fossen; Ray Rees; Davud Rostam-Afschar; Viktor Steiner (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2017)
We investigate how personal income taxes affect the portfolio share of personal wealth that entrepreneurs invest in their own business. In a reformulation of the standard portfolio choice model that allows for underreporting of private business income to tax authorities, we show that a fall in the tax rate may increase investment in risky entrepreneurial business equity at the intensive margin, but decrease entrepreneurial investment at the extensive margin. To test these hypotheses, we use household survey panel data for Germany eliciting the personal wealth composition in detail in 2002, 2007, and 2012. We analyze the effects of personal income taxes on the portfolio shares of six asset classes of private households, including private business equity. In a system of simultaneous demand equations in first differences, we identify the tax effects by an instrumental variables approach exploiting tax reforms during our observation period. To account for selection into entrepreneurship, we use changes in entry regulation into skilled trades. Estimation results are consistent with the predictions of our theoretical model. An important policy insight is that lower taxes drive out businesses that are viable only due to tax avoidance or evasion, but increase investment in private businesses that are also worthwhile in the absence of taxes.
urn:nbn:de:bsz:100-opus-13815
Keywords: H24; H25; H26; L26; G11; 330; taxation; entrepreneurship; portfolio choice; investment